Paulo Freire's Critical Pedagogy Analysis Of Educational Transformation - Nugraha, Asep Eka; Wibowo, Deki; Hendrawan, Budi (MSJ : Majority Science Journal, 2024)
The purpose of this study described critically in several aspects of Paulo Freire's critical pedagogy and its contribution to educational transformation. This study uses a qualitative approach with the literature study method, namely the data collection method by understanding and studying the theory of various literature related to research. This research is based on critical interpretation. This illustrates several aspects of Paulo Freire's book, The Pedagogy of the Oppressed. In addition, several other related sources are also considered as a basis. This research is based on the concept of several key terms, to draw conclusions based on several important Freire messages. The results showed that, (1) Provides a background in critical thinking, the theoretical basis of Freire's critical pedagogy, and his life experience. Freire's critical thinking about the "bank style" education system, which hinders the development of students' creative thinking. This includes the role of oppression and dehumanization of the traditional education system and "bank style", dialogue and awareness, the implementation of education raises problems, praxis as an election in situations, the role of political and cultural factors in changes in education. (2), based on Freire's critical pedagogy, there is a critical interpretation of the current school system education process, practicing teaching strategies based on freedom, curriculum planning, and the possibility of transformation become the role of teachers and students. Therefore, to prepare citizens based on freedom and humanity, it is necessary for students to have a critical pedagogical method that can move forward by building relationships between students and their environment. This requires collaborative and interactive policies and teaching. It is hoped that this research will provide some encouragement for the transformation of the current state of education.